1992
DOI: 10.1111/j.1365-2044.1992.tb04194.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of blood lactate concentrations, oxygen delivery and oxygen consumption in septic shock and the adult respiratory distress syndrome

Abstract: SummaryTissue hypoxia is thought to be pivotal to the development of multiple organ failure, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
11
0
3
Order By: Relevance
“…No entanto, é importante salientar que na sepse também pode haver perfusão tecidual inadequada na ausência de sinais clínicos (hipoperfusão oculta). O seu mecanismo não está completamente esclarecido, porém pode ser uma combinação de fatores, como alteração da distribuição de fluxo sangüíneo pela vasodilatação, bem como aumento da distância para difusão entre o capilar e a célula, ocasionado pelo edema intersticial, associado à lesão do capilar 15 . Dos oito casos de sepse, apenas um não apresentou aumento do lactato.…”
Section: Discussionunclassified
“…No entanto, é importante salientar que na sepse também pode haver perfusão tecidual inadequada na ausência de sinais clínicos (hipoperfusão oculta). O seu mecanismo não está completamente esclarecido, porém pode ser uma combinação de fatores, como alteração da distribuição de fluxo sangüíneo pela vasodilatação, bem como aumento da distância para difusão entre o capilar e a célula, ocasionado pelo edema intersticial, associado à lesão do capilar 15 . Dos oito casos de sepse, apenas um não apresentou aumento do lactato.…”
Section: Discussionunclassified
“…Esse fato já está descrito e é explicado pelo aparecimento de uma resposta hemodinâmica compensatória 16 . Nos casos em que essa resposta não pode ser constatada, o nível de lactato permanece alto ou aumenta na evolução com 100% de mortalidade 15 .…”
Section: Discussionunclassified
“…Its mechanism has not been clearly described, but it may involve a combination of factors such as a change in the distribution of blood flow by vasodilation, or an increase in the diffusion distance between the capillary and the cell as a result of interstitial edema, associated with capillary injury. 15 Of the eight sepsis cases, only one did not have high levels of lactate. This fact has already been described and may be explained by the development of a compensatory …”
Section: Resultsmentioning
confidence: 99%
“…16 In the cases in which such response cannot be detected, lactate level remains elevated or increases during hospitalization leading to a 100% mortality rate. 15 These findings led intensivists to check whether lactate concentration, besides being clinically useful as an indicator of circulatory involvement and of the oxygenation state, could also be used as prognostic marker for the risk of death among critically ill patients. 5,16,17 Hyperlactatemia has been detected in critically ill patients and several clinical studies have shown an association between its levels and the type of outcome, with higher levels in those patients who will eventually die.…”
Section: Discussionmentioning
confidence: 99%